Juanita - Tonos, Leticia; Koldo; García, Cheddy; Valverde, Fernando, 1951-; Sánchez, Carasaf; Quezada, Milly, 1952- (Producciones Línea Espiral ; Albero Producciones, 2018)
Juanita, an ingenious Dominican immigrant who returns to her country after living 5 years in Spain, but does not return alone, is accompanied by Mariano, a rough Spanish farmer who has decided to sell her house in Chinchón and move to the Caribbean. Juanita and Mariano, who while in Spain will cling to each other like two castaways to a lifeguard, will look for ways not to drown in Santo Domingo this Christmas. --